Literatura, aprendizagem significativa e pedagogia da alternância: um olhar sobre ações pedagógicas voltadas a educação do campo - Tonetto, Isadora Raddatz (2023)
This research was presented to the Master's in Education course, of the Postgraduate Program in Education, research line LP2: Public Educational Policies, educational practices and their interfaces, at the Federal University of Santa Maria. We sought to analyze the pedagogical actions developed in two schools in rural areas in the interior of Rio Grande do Sul, in two different cities. To this end, municipal public elementary schools were selected with the aim of answering the following research problem: How are pedagogical actions developed in schools in rural areas in the interior of Rio Grande do Sul? To answer this question, the qualitative approach methodology was used in addition to the methodology of (auto)biographical narratives, using semi-structured interviews as technical instrumentation. It is noteworthy that the rural environment is often characterized by cooperation and solidarity between members of the school community, and the knowledge of rural schools is contradictory to urban hegemony, as they are traditional, with family-local transmission, studying them is the opportunity to learn experiences, traditions and history that go beyond school training, are capable of qualifying teaching and student practices regarding the learning process. By adopting a pedagogical approach that encourages collaboration and teamwork, Escola do Campo strengthens values, while enriching the teaching-learning process. In this way, rural education is a social movement and a political act that seeks social inclusion, the recognition of constitutionally already acquired rights. This study comprised the evolution of public policies, educational practices in the process of forming basic education, the main concepts related to rural education, pedagogical actions and constitutional provisions on the topic. It was also possible, through (auto)biographical narratives, to learn about teaching experiences regarding pedagogical actions in rural schools. As a result of this research, literature, meaningful learning and alternation pedagogy were found to be important pedagogical actions in the training of students at rural schools. Through the narratives and data analyzed, the results obtained prove the importance of such actions in the construction of knowledge aimed at students in rural areas. The limitations observed refer to the lack of attention from public authorities with school infrastructure, the lack of secondary education in the localities, and the lack of public policies with such purposes